EFFECT OF THE ASSETS STRUCTURE, GROWTH OPPORTUNITY, AND SYSTEMATIC RISK ON CAPITAL STRUCTURE AND CAPITAL STRUCTURE EFFECT ON COMPANY VALUE - Desliniati, Nurfitri; Sundiman, Didi (Journal of Management and Business, 2016)
This study aimed to examine the effect of capital structure, growth opportunity, and the systematic risk ofthe capital structure and the effect of capital structure on firm value. The dependent variable in this studyis the value of the company on the capital structure, while independent variables used is the capitalstructure, growth opportunity, and the systematic risk.Research using secondary data source dataoriginating from the Indonesian Stock Exchange (BEI) and yahoo finance. Sampling using purposivesampling method. So from 55 companies property, real estate, and construction of 37 companies in thesample taken in the period 2010-2014 with a total of 185 observations. The data used in this study is adata panel. Data analysis using Eviews 6.0 program. Data analysis technique used is panel dataregression analysis with fixed effect models method (FEM).The results showed that during the studyperiod from 2010 to 2014 in partial capital structure have significant and positive effect on the capitalstructure, while the growth opportunity and systematic risk and no significant effect on the capitalstructure. Capital structure have significant and positive effect on firm value.